Examining Constraints: A Critical Appraisal of Autoimmune Diseases and Facial Aging Study [Letter] - Shuja MH; Hasan M (Dove Medical Press, 2024)
Muhammad Hamza Shuja, Minal Hasan Dow Medical College, Karachi, Sindh, PakistanCorrespondence: Muhammad Hamza Shuja, Dow Medical College, Dow University of Health Sciences, Baba-e-Urdu Road, Karachi, 74200, Pakistan, Tel +923316079762, Email hamzashuja9825@gmail.com